2000
DOI: 10.1111/j.1741-3737.2000.01208.x
|View full text |Cite
|
Sign up to set email alerts
|

Research on Household Labor: Modeling and Measuring the Social Embeddedness of Routine Family Work

Abstract: ࡗ Research on Household Labor: Modeling and Measuring the Social Embeddedness of Routine Family Work This article reviews more than 200 scholarly articles and books on household labor published between 1989 and 1999. As a maturing area of study, this body of research has been concerned with understanding and documenting how housework is embedded in complex and shifting social processes relating to the well-being of families, the construction of gender, and the reproduction of society. Major theoretical, method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

83
1,529
11
142

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,416 publications
(1,765 citation statements)
references
References 217 publications
(458 reference statements)
83
1,529
11
142
Order By: Relevance
“…The composite index also confirms that women do significantly more housework than men do in all of the three communities (total composite index=73.22 for men and 196.38 for women, t=−78.79, p=0.000). This finding is in accordance with the literature on the existing imbalance in the division of housework, which remains primarily women's responsibility (Coltrane, 2000;Demo & Acock, 1993;Hossain & Roopnarine, 1993;Starrels, 1994;Twiggs et al, 1999;Van Willigen & Drentea, 2001). The results also confirm previous findings on the division of housework among men and women aged 5 years and older in Hay el Sellom, Nabaa, and Burj Barajneh Camp, which revealed that housework is feminized, not only in adulthood, but also in the early stage of childhood (Habib, Nuwayhid, Merhi, & Myntti, 2005).…”
Section: Housework and Gendersupporting
confidence: 91%
See 2 more Smart Citations
“…The composite index also confirms that women do significantly more housework than men do in all of the three communities (total composite index=73.22 for men and 196.38 for women, t=−78.79, p=0.000). This finding is in accordance with the literature on the existing imbalance in the division of housework, which remains primarily women's responsibility (Coltrane, 2000;Demo & Acock, 1993;Hossain & Roopnarine, 1993;Starrels, 1994;Twiggs et al, 1999;Van Willigen & Drentea, 2001). The results also confirm previous findings on the division of housework among men and women aged 5 years and older in Hay el Sellom, Nabaa, and Burj Barajneh Camp, which revealed that housework is feminized, not only in adulthood, but also in the early stage of childhood (Habib, Nuwayhid, Merhi, & Myntti, 2005).…”
Section: Housework and Gendersupporting
confidence: 91%
“…Previous researchers have used different ways to assess housework (Coltrane, 2000;Nakhaie, 1995;Twiggs et al, 1999). There is evidence that time spent doing a chore by itself is not enough to analyze the contributions of men and women to household labor, but rather, in addition to the type of chore, one must also take into account the frequency with which it is performed (Baxter, 2002;Twiggs et al, 1999).…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…She seemed to be more satisfied when confirming her traditional role at home, while he was not concerned about this issue, as in the world-wide studies (e.g. Coltrane, 2000).…”
Section: Woman Is Seen As Responsible For Houseworkmentioning
confidence: 94%
“…Rutyna jest kobietą. To kobiety zwykle wykonują te czynności, które muszą być zrobione, w dodatku (niemal) codziennie, i istnieje mała elastyczność co do tego, kiedy w ciągu dnia muszą być one wykonane [Coltrane 2000]. W efekcie kobiety gotują, sprzątają, piorą, ubierają dzieci i je karmią.…”
Section: Doing Genderunclassified